Outcomes of Primary Versus Delayed Primary Stump Closure in Post-Traumatic Below-Knee Amputations: A Surgical Perspective - Umer, Yasir; Ismail , Syed Junaid; Nisar, Aamer; Junaid, Nida; Umer, Waleed (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the outcomes of primary and delayed primary closure of stump after traumatic below-knee amputation (BKA).Study Design: Quasi-experimental study.Place and Duration of Study: Orthopedic Surgery Department of Ali Medical Centre Islamabad, Pakistan, from Jan 2022 to Jun 2023.Methodology: Eighty (n=80) patients who underwent traumatic below-knee amputation (BKA) were included, and divided into two groups. Group-A patients underwent primary stump closure and Group-B patients underwent delayed primary stump closure. Patients underwent surveillance after the procedure, and variables including length of hospital stay, reoperation and wound infection were noted in both groups.Results: The mean age of patients was 38.65±0.65 years. 71(88.8%) patients were males while 9(11.3%) were females. The mean length of hospital stay in Group-A was 6.17±2.74 days and in Group-B group was 8.42±1.48 days (p